An optimal growth pattern during pregnancy and early childhood associates with better fertility in men. Issue 6 (22nd November 2022) - Laru, Johanna; Ojaniemi, Marja; Franks, Stephen; Järvelin, Marjo-Riitta; Korhonen, Elisa; Piltonen, Terhi T; Sebert, Sylvain; Tapanainen, Juha S; Morin-Papunen, Laure
Abstract: Objective: This study aimed to evaluate the association between birth weight (BW), childhood and adolescent BMI, with reproductive capacity in men. Design: A prospective, population-based cohort study (Northern Finland birth cohort 1966). Methods: Around 6196 men born in 1966 were followed from birth to age 50 years. Weight and height were measured repeatedly by professionals. Reproductive capacity (infertility assessment, male factor infertility and infertility treatment by age 46 years) was evaluated by questionnaires at ages 31 and 46 years. The number of children by the age of 50 years was recovered from registers. After excluding the men who reported never having attempted to have children or not answering the question at age 31 or 46 years ( n  = 2041), 4128 men were included in the final study population. Results were adjusted for BW, BW for gestational age (GA), mother's smoking status, marital status, educational level and smoking status. Results: Being small for GA (10.5% vs 8.2%, P  = 0.012) or having a lower BW (3495 g vs 3548 g, P  = 0.003) were associated with childlessness. The association was however no longer significant after adjusting for marital status. Being underweight in early childhood was associated with an increased risk of infertility assessment (adjusted, aOR: 2.04(1.07–3.81)) and childlessness (aOR: 1.47(1.01–2.17)) compared to the normal weight group. Conversely, overweight or obesity in early childhood was associated with a decreased risk of infertility assessment (aOR: 0.60 (0.41–0.87)), treatment (aOR: 0.42 (0.25–0.70)) and male factor infertility (aOR: 0.45 (0.21–0.97)). BMI in mid-childhood or puberty had no association with infertility or childlessness. Conclusion: In boys, an optimal growth trajectory during pregnancy and early childhood seems to be very important for life-long fertility.